Evaluando de cosecha oculta de los bosques: metodos de valuacion para bosques y recursos forestales - Campbell, Bruce M.; Luckert, M.K. (Nordan-Comunidad, 2002)
This study examines the preliminary impacts of Indonesia's decentralization process on the administration and management of forest resources in Ketapang District, West Kalimantan. The case study is based on field work carried out in mid-2000, using a rapid appraisal methodology. The report covers the impacts of decentralization in three areas, in particular: customary adat communities, oil palm and rubber plantations, and conservation issues related to Gunung Palang National Park. In each of these areas, the authors examine struggles among competing interest groups that have arisen under decentralization. The study finds that with the shift of administrative authority to the district level, the district government in Ketapang took measures to generate local sources of revenues by issuing large numbers of small-scale timber extraction permits and to 'legalize' the transport of timber that had otherwise been harvested illegally. The study also finds that the very limited flow of formal revenues from the Gunung Palang National Park to the district government has encouraged an escalation of illegal logging within the park's boundaries. The authors recommend that the Ketapang District government become more involved in administering the national park to ensure that economic interests of both the district government and local communities are accomodated in the park's management.